THE EFFECT OF USING VIDEO LISTEN-READ-DISCUSS STRATEGY TOWARD STUDENT’S READING COMPREHENSION OF RECOUNT TEXT AT THE SECOND GRADE OF SMP MUHAMMADIYAH RAMBAH - Evi Kasyulita; Rivi Antoni; Nur Syafitri (English Study Program University of Pasir Pengaraian, 2020)
The purpose of this research were to find out students reading comprehension of recount text taught through LRD strategy and taught without using LRD strategy. And to find out whether there was an effect of using LRD strategy toward students reading comprehension of recount text at the second grade of SMP MuhammadiyahRambah. This research was an experimental research, precisely a quasi experimental research. The instrument of this research was multiple choices test of reading comprehension. The participants were students at second grade of SMPMuhammadiyah Rambah. The researcher findings showed that the improvement from the score of t-test. The total score of t-test was 3.451.Based on p-value was 0.003 < 0.05. Therefore, it could be concluded that there was an effect of using LRD strategy toward students reading comprehension of recount text at the second grade students of SMP Muhammadiyah Rambah.